East African Community: Demographics and Economic Development - D. V. Kuzmin (Informaciâ i Innovacii)
Regional economic integration in East Africa, as in sub-Saharan Africa as a whole, remains an urgent task for States. It also arouses the interest of researchers for its features. The basis of regional economic integration in the associations of Africa in the XXI century is a stable macroeconomic dynamics, since the author proceeds from the fact that in the conditions of economic recovery, integration processes in the region are intensified. At the same time, the author believes that the socio- economic problems common to the countries of Africa or its individual regions can also serve as a basis for the activation of integration processes.